Komposisi Jenis dan Struktur Komunitas Ikan di Ekosistem Lamun Pantai Sindhu, Sanur, Bali - Kolis Pratama; I Wayan Arthana; Dewa Ayu Angga Pebriani (Journal of Marine and Aquatic Sciences, 2020)
Sindhu Beach is one of the beaches which located in Sanur. The coastal areas of Sindhu Beach has long been used for various economic activities, such as recreation areas or marine tourism. So that these activities can adversely affect the sustainability of the seagrass ecosystem as a habitat for various types of aquatic biota, especially fish. This study aims to determine the composition of fish community species and structures, to know the types of seagrass, and also to know the condition of water quality in the seagrass ecosystem of Sindhu Beach, Sanur, Bali. This study has been conducted from January to February 2018 by direct observation method. The results of the composition of fish species as a whole found 537 of fish that consisting of 22 species and it came from 11 families. The overall value of community structure is obtain by the value of the diversity index (H') of 2.68, uniformity index (E) 0.87, and the dominance index (C) 0.09. The types of seagrasses which found in the study location was consist of 8 species of seagrass covering Enhalus acoroides, Syringodium isoetifolium, Halodule pinifolia, Halodule uninervis, Thalassia hemprichii, Cymodocea rotundata, Halophila ovalis, and Halophila spinulosa. The result of measurement of water quality parameters from all stations were obtain the average measurement of dissolved oxygen 7,1 mg / l, salinity 30o/oo, pH 8,24, and temperature 29,80C. The result of measurement of water quality parameter shows that the condition of seagrass ecosystem of Sindhu Beach was still considered optimal for marine life.